LAND GRABBING FOR AGRO-EXTRACTIVISM IN THE SECOND NEOLIBERAL PHASE IN BRAZIL/Estrangeirização da terra para o agroextrativismo na segunda fase neoliberal no Brasil/ El acaparamiento de tierras para el agro-extractivismo en la segunda fase neoliberal en Brasil (REVISTA NERA, 2019)
Building territorial policies to free lands for national and international corporations to produce large-scale commodities for export, called agro-extractivism is one of the components of the neoliberal agrarian question. In Brazil, in the last thirty years, the agrarian question had two phases: the Neoliberal and the post-neoliberal. These policies intensified the territorial disputes between the agribusiness corporations and the peasant, indigenous and quilombola movements. To better understand these disputes we analyze the new conflicts from the reading of Brazil agrarian and rural Brazil. Through the method of paradigmatic debate, we analyze theoretical and political references for territorial development. Conflictuality is analyzed on a national scale with emphasis on new territory: MATOPIBA, created exclusively for agribusiness, is territorialized and attracts interest from several companies and international financial capital. Another case that we analyze is the conflict between the Landless Rural Workers Movement (MST) and Del Monte Corporation in the territorial dispute in the Apodi plateau in the state of Ceará. We analyze the hegemony of Agrarian capitalism in the neoliberal and post-neoliberal phases and the actions of the peasantry to resist and advance, facing the binomial latifundio-agribusiness. With this article, we contribute to updating the readings on the Brazilian agrarian question.